If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -8) + -1(x + -4) = 3(x + 5) + -3 Reorder the terms: 2(-8 + x) + -1(x + -4) = 3(x + 5) + -3 (-8 * 2 + x * 2) + -1(x + -4) = 3(x + 5) + -3 (-16 + 2x) + -1(x + -4) = 3(x + 5) + -3 Reorder the terms: -16 + 2x + -1(-4 + x) = 3(x + 5) + -3 -16 + 2x + (-4 * -1 + x * -1) = 3(x + 5) + -3 -16 + 2x + (4 + -1x) = 3(x + 5) + -3 Reorder the terms: -16 + 4 + 2x + -1x = 3(x + 5) + -3 Combine like terms: -16 + 4 = -12 -12 + 2x + -1x = 3(x + 5) + -3 Combine like terms: 2x + -1x = 1x -12 + 1x = 3(x + 5) + -3 Reorder the terms: -12 + 1x = 3(5 + x) + -3 -12 + 1x = (5 * 3 + x * 3) + -3 -12 + 1x = (15 + 3x) + -3 Reorder the terms: -12 + 1x = 15 + -3 + 3x Combine like terms: 15 + -3 = 12 -12 + 1x = 12 + 3x Solving -12 + 1x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 1x + -3x = 12 + 3x + -3x Combine like terms: 1x + -3x = -2x -12 + -2x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + -2x = 12 + 0 -12 + -2x = 12 Add '12' to each side of the equation. -12 + 12 + -2x = 12 + 12 Combine like terms: -12 + 12 = 0 0 + -2x = 12 + 12 -2x = 12 + 12 Combine like terms: 12 + 12 = 24 -2x = 24 Divide each side by '-2'. x = -12 Simplifying x = -12
| -x=-30/-5 | | 3y-3=8x-4 | | Y=-5x^2-2x+2 | | 3x-2=3(y-2) | | n/3-4.6=21.6 | | 10-2x^2=-98 | | 12:18/7 | | 2(2x+3)=5x-5 | | 3x+2y+3z=2 | | 2.4=108 | | X^5=4+3logx | | z=1.95 | | 12/1:18/7 | | m+3=2m-1 | | 7/8=3/x-6 | | 3x-2+y-2=60 | | -3x=-12+-10 | | 4(6t+4)=4(5t-5) | | 6r-(r+3)=10-(7-5r) | | 7v/8=21 | | X/4-x/12=2 | | 2x-y+z=-11 | | -1+2x=28+13 | | t/6-2=11 | | kx-3=5 | | u/7=17.92 | | P=344x-560 | | 8v=20.40 | | 3n+8+12n-5-7n+11= | | X-11/2=9 | | 7x=2/3 | | 8/1=.22/n |